Left Ventricular Remodeling after Percutaneous Coronary Intervention in Acute Myocardial Infarction Complicated by Acute Heart Failure - Obertynska, Oksana G.; Rasputina, Lesia V.; Didenko, Daria V.; Solomonchuk, Andrii V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To establish the relationship between structural-functional and laboratory parameters in patients with myocardial infarction (MI) and heart failure (HF) undergoing percutaneous coronary intervention (PCI). Materials and methods. We examined 308 MI patients who were divided into 3 groups: 161 patients without signs of acute heart failure (AHF) (group I), 99 with Killip class II-III AHF (group II) and 48 with Killip class IV (cardiogenic shock) (group III). All the patients underwent general clinical examinations: complete blood count, lipid profile, creati-nine, quantitative determination of troponin I, D-dimer, creatine kinase-MB, electrocardiography, coronary angiography with PCI, focused cardiac ultrasound and standard echocardiography over 3-5 days. Results. According to the focused cardiac ultrasound, the majority of MI patients with signs of AHF had preserved left ventricle function, and only 8.2% of patients had left ventricle ejection fraction (LVEF) ˂40%. The most significant structural and functional changes were observed in group II. After PCI, a significant increase in left ventricle contractility was found in all groups, but in the group II, the increase in LVEF was more pronounced. The severity of HF manifestations increased depending on the severity of diastolic dysfunction. Many correlations were established: an inverse relationship between LVEF and the presence of HF, the number ofaffected vessels, proximal left anterior descending artery lesions, low-density lipoprotein cholesterol, and atrium fibrilla-tion; a direct relationship between LVEF and hemoglobin levels and glomerular filtration rate. Conclusions. The vast majority of patients with MI and signs of AHF had preserved left ventricle contractile function. High-grade HF manifestations increase depending on the severity of diastolic dysfunction. Myocardial revascularization in MI pa-tients significantly improves functional and volumetric parameters of myocardial function. Numerous correlations between structural-functional and laboratory parameters in patients with MI and HF who underwent PCI have been established.